Perceived strategies to reduce traumatic childbirth amongst Iranian childbearing women: a qualitative study - Mahshid Taheri; Ziba Taghizadeh; Nahid Jafari; Amirhossein Takian (BMC, 2020)
Abstract Background Psychological birth trauma (PBT), mainly due to overlooking maternal mental health, is a common and high prevalence public health problem in low-resource settings. Preventing PBT is a good indicator of the realization of human rights in healthcare. This work reports the results of a qualitative study that aimed to identify perceived strategies of PBT prevention among childbearing women in Iran. Methods We conducted semi-structured in-depth interviews with 22 mothers with history of traumatic childbirth, two mothers with positive childbirth experience, two spouses, and eight health professionals between April and June 2017. We used purposive sampling method to recruit traumatized mothers, while health experts were selected based on their relevant expertise and experience. Our initial literature review identified eight categories, using which we developed our interview guide and conducted the content analysis approach. Results With the maximum possible purification, we reached 50 thematic codes. The strategies to prevent PBT are generally summarized in four major themes and 13 categories: 1) skill-builder knowledge [Birth preparedness, Mothers' empowerment in maintaining mental health, Understanding the importance of mental care in maternity services], 2) responsible caregiving [Support loop, Good behavior of the caregivers, Deepening trust, Struggle with medicalization of childbirth, Labour pain relief, Special services for maternal mental health], 3) the alliance of prenatal and antenatal care [Continuity of care, Coordination of prenatal and antenatal caregivers], and 4) reconstruction of the structures [Efficient management, Rebuilding physical structures]. Conclusions This is a comprehensive approach towards PBT prevention, which can guide future efforts to reduce PBT at the clinical level and open further avenues for future studies. We recommend policy makers to consider the integration of multilevel and multidimensional PBT prevention interventions, simultaneously within maternity care services packages for promotion of mental health.